2009
DOI: 10.1002/rcm.3965
|View full text |Cite
|
Sign up to set email alerts
|

A tandem mass spectrometric approach to the identification of O‐glycosylated glargine glycoforms in active pharmaceutical ingredient expressed in Pichia pastoris

Abstract: Glycoforms of glargine expressed in Pichia pastoris were isolated by high-performance liquid chromatography and analyzed by a series of chemical and mass spectrometric methods for the identification of various glycoforms, glycosylation position, nature and structure of glycans. Reduction and alkylation, peptide mapping techniques were used to decipher the amino acid site at which glycosylation had taken place. Chemical methods were coupled with mass spectrometry techniques such as electrospray ionization and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The mannosylated impurities in insulin analog, insulin glargine, have been previously characterized [6]. A similar approach was taken for the characterization of these impurities in recombinantly produced insulin where we enriched the mono-mannosylated and di-mannosylated insulin which are insulin molecules attached with one and two mannose moieties, respectively.…”
Section: Characterization Of the O-mannosylated Impurities In Insulinmentioning
confidence: 99%
See 3 more Smart Citations
“…The mannosylated impurities in insulin analog, insulin glargine, have been previously characterized [6]. A similar approach was taken for the characterization of these impurities in recombinantly produced insulin where we enriched the mono-mannosylated and di-mannosylated insulin which are insulin molecules attached with one and two mannose moieties, respectively.…”
Section: Characterization Of the O-mannosylated Impurities In Insulinmentioning
confidence: 99%
“…A similar approach was taken for the characterization of these impurities in recombinantly produced insulin where we enriched the mono-mannosylated and di-mannosylated insulin which are insulin molecules attached with one and two mannose moieties, respectively. This was achieved by fractionating the corresponding peaks in the analytical RP-HPLC peak [6] and pooling multiple runs of the same.…”
Section: Characterization Of the O-mannosylated Impurities In Insulinmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was reported that insulin glargine expressed in Pichia pas toris (a yeast)-that normally is not glycosylated-had 3 sugar molecules (mannose) attached to it as the result of a different manufacturing process employed by 1 manufac turer of recombinant insulins. 6 The publication refers to an experimental glycosylated product; however, also a pub lished analysis of the glargine marketed by Biocon showed that this is glycosylated. 7 The issue is that even "minor" differences/changes in the manufacturing process may have considerable (potentially clinically relevant) effects on the biological effects induced by such insulins.…”
Section: Insulin Manufacturingmentioning
confidence: 99%